CO-EXPRESSION OF INOS AND HSP70 IN DIABETES TYPE 1 MAKES A RATIONAL HYPOTHESIS TO EXPLAIN THE DIABETIC NEUROPATHY - Al-khatib, Ahed (European Scientific Journal, ESJ, 2013)
ï»¿The present study explores the co-expression of iNOS and HSP70 in brains of diabetic rats. Methodology involved induction of diabetes type 1 in rats and carrying out immunohistochemical analysis for both iNOS and Hsp70 in the brain tissues. Results revealed that the levels of HSP70 decreased in diabetes type 1 significantly compared with baseline levels for control groups, while the level of iNOS increased dramatically in brain tissue of diabetic rats. Furthermore, the data of the present study showed similar levels of HSP70 and iNOS at baseline level. The expression and localization of iNOS have both shifted in brain of control group from gray matter to white matter in rat diabetic brain. Conclusions: the imbalance of molecular expression of iNOS and HSP70 offers better molecular environment to facilitate pathogenesis of diabetes and explain partly that the overexpression of iNOS downregulates the expression of HSP70.